ANALISIS PELAYANAN DAN BAGI HASIL TERHADAP KEPUTUSAN MENABUNG NASABAH PADA BANK SYARIAH DI KOTA MEDAN - Daulay, Raihanah (JURNAL ILMIAH MANAJEMEN & BISNIS, 2010)
This research is aimed to know the effect of service and profit sharing to the customerâs saving decision at Medan Chief Branch Office of Syariah Medan Bank and also to know the most dominantÂ  factor which affects the customerâs saving decision. This research is a descriptive research with study case approach supported by survey method. The result ofÂ  F-test and t-testÂ  indicated that service and profit sharing have positive effect and significant to customerâs saving decision in Medan Chief Branch Office of Syariah Bank.. Based on theÂ  standardized coefficient, it can be known that belief variable partially has dominant effect than service and profit sharing variables. The adjusted R square regression result is 36,2 % which showed that independent variableÂ Â Â  (service and profit sharing) can explain 36,2 % to dependent variable (saving decision).